Analisis Pengaruh Pengeluaran Pemerintah, Inflasi, dan Pertumbuhan Penduduk Terhadap Pertumbuhan Ekonomi di Sumatera Utara - Sagala, Santi Monika; Rizal, Yani; Mizwar, Mizwar (Jurnal Ilmu Ekonomi, 2025)
This study aims to analyze the influence of government expenditure, inflation, and population growth on economic growth in North Sumatra Province. The data used are annual secondary data from 2009 to 2023 obtained from the Central Bureau of Statistics (BPS). The analytical method applied is multiple linear regression using the natural logarithm approach. The results show that partially, government expenditure has a positive and significant effect on economic growth. Inflation has a negative but insignificant effect, while population growth has a negative and significant effect on economic growth. Simultaneously, all three independent variables significantly affect economic growth in North Sumatra Province. These findings indicate that government spending is an important fiscal tool to boost economic growth, while uncontrolled population growth can hinder it. This research is expected to serve as a reference for local governments in formulating sustainable and data-driven economic development policies.